2004
DOI: 10.1038/nm1000
|View full text |Cite
|
Sign up to set email alerts
|

PKC-α regulates cardiac contractility and propensity toward heart failure

Abstract: The protein kinase C (PKC) family of serine/threonine kinases functions downstream of nearly all membrane-associated signal transduction pathways. Here we identify PKC-alpha as a fundamental regulator of cardiac contractility and Ca(2+) handling in myocytes. Hearts of Prkca-deficient mice are hypercontractile, whereas those of transgenic mice overexpressing Prkca are hypocontractile. Adenoviral gene transfer of dominant-negative or wild-type PKC-alpha into cardiac myocytes enhances or reduces contractility, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
505
5
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 538 publications
(554 citation statements)
references
References 29 publications
35
505
5
3
Order By: Relevance
“…Calcineurin dephosphorylates the nuclear factor of activated T cells, which then translocates to the nucleus, interacts with the cardiac zinc finger transcription factor (GATA4),34 and orchestrates the reactivation of fetal genes such as natriuretic peptides and alpha‐skeletal muscle actin, which were increased in all phenotypes here. Calcineurin also activates protein kinase C,40 and activated protein kinase C in cardiac stress37 phosphorylates and inhibits inhibitor 1, leading to phospholamban dephosphorylation and inhibition of SERCA2a activity. Interestingly, despite enhanced expression of fetal genes in all phenotypes, p‐phospholamban, S16 was increased in the CR and MILD phenotypes and decreased in the MOD phenotype only.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin dephosphorylates the nuclear factor of activated T cells, which then translocates to the nucleus, interacts with the cardiac zinc finger transcription factor (GATA4),34 and orchestrates the reactivation of fetal genes such as natriuretic peptides and alpha‐skeletal muscle actin, which were increased in all phenotypes here. Calcineurin also activates protein kinase C,40 and activated protein kinase C in cardiac stress37 phosphorylates and inhibits inhibitor 1, leading to phospholamban dephosphorylation and inhibition of SERCA2a activity. Interestingly, despite enhanced expression of fetal genes in all phenotypes, p‐phospholamban, S16 was increased in the CR and MILD phenotypes and decreased in the MOD phenotype only.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Molnar et al (2009) showed a significant increase in PKCα binding to the cardiomyofilament contractile proteins following application of Ca 2+ (Molnar et al 2009), indicating a role for PKCα-mediated phosphorylation on myofilament contractile function. Braz et al (2004) stated that PKCα is also localized in a weak sarcomeric pattern in unstimulated adult cardiac myocytes and that upon stimulation with phorbol myristate acetate, PKCα translocates to the Z-lines and the T-tubular network.…”
Section: Activation and Distribution Of Pkc Isoformsmentioning
confidence: 99%
“…In transgenic mice over-expressing PKCα, Braz et al (2004) observed signs of cardiac hypertrophy at the age of 8 months. PKCα directly phosphorylated I-1 and thereby altered the activity of protein phosphatase-1 (PP-1).…”
Section: Activation and Distribution Of Pkc Isoformsmentioning
confidence: 99%
See 2 more Smart Citations